Copper translocation and tolerance in seedlings of tree species grown in contaminated soil - Silva,Rodrigo F. da (2015)
ABSTRACTHigh concentrations of copper (Cu) may be toxic to plants, yet some species can be tolerant to soils contaminated by this metal. The study aimed to evaluate Cu translocation and tolerance in seedlings of ‘timbaúva’ (Enterolobium contortisiliquum (Vell.) Morong), ‘pata-de-vaca’ (Bauhinia forficata Link) and ‘amendoim-bravo’ (Pterogyne nitensTul) subjected to Cu-contaminated soil. The study was conducted in a greenhouse for 120 days, using as substrate a clayey Oxisol. The experiment was set in a completely randomized design, using a 3 x 6 factorial scheme, corresponding to three forest species (‘timbaúva’, ‘pata-de-vaca’ and ‘amendoim-bravo’) and six Cu doses in the soil (0, 60, 120, 180, 240 and 300 mg kg-1), with six replicates. The following variables were analysed: total dry matter, Cu content and its accumulation in roots and shoots, tolerance and translocation indices and the coefficient of impact of the contamination on the relative contents of Cu in roots and shoots. ‘Timbaúva’ showed lower reduction in total dry matter with the increase of Cu doses in the soil, proving to be able to decrease Cu translocation to the shoots and tolerate doses of up to 236 mg kg-1 of this metal in the soil. ‘Timbaúva’ seedlings are more tolerant to contamination of Cu in soil, compared with seedlings of ‘amendoim-bravo’ and ‘pata-de-vaca’.